HUBUNGAN PARITAS DENGAN KEJADIAN ROBEKAN JALAN LAHIR PADA IBU BERSALIN DI BPM NI LUH MARIYANI Amd.Keb KECAMATAN SAWAN TAHUN 2018 - Adawiyah, Rabiatul; Fatmawati, Zeny; Fatmwati, Istiadah (LPPM STIKES HUSADA JOMBANG, 2020)
Introduction: Tearing of the birth canal is a birth canal injury that occurs at the time of birth of the baby either using the tool or not using the tool. Injury or rupture during labor is the second most common cause of postnatal bleeding. Vaginal delivery is often accompanied by rupture. In some cases the rupture becomes more severe, the vagina undergoes laceration and the perineum is often torn primarily on primigravids, tears may occur spontaneously during vaginal delivery. Method: in this research is correlation analysis research, this research design use Cross sectional approach. The sample of 127 people. Sampling technique used is nonprobability sampling with total sampling techniqu. Result: of 127 respondents can be seen that most of the parity 2-4 times in spontaneous maternal mothership in BPM Ni Luh Mariyani Amd.Keb 2017, that is as much as 63 respondents (49.6%), while the least are respondents with parity> 4 times , As many as 8 respondents (6.3%) and 127 respondents can be seen that most degree of perinium degree degrees 2 that is as many as 90 respondents (70.9%). While as many as 18 respondents (14.2%) perinium degree per Discussion: is that the result of Spermank Rho correlation test obtained that ρ = 0.001 meaning 0.001 <α 0.05 means that H0 is rejected, Ha is accepted which means there is a parity relationship with the occurrence of tear on spontaneous birth mothers in BPM Luh Mariyani 2017.